Odpowiedzi

Najlepsza Odpowiedź!
2009-12-28T15:53:55+01:00
A) 3x-3(2x-2) = 3(x-2)
3x-6x+6=3x-6
3x-3x-6x=-6-6
-6x=-12
x=2
c)-5x+2(1-x) = -x-2(x-1)
-5x+2-2x=-1-2x+2
-5x-2x+2x=-2+1+2
-5x=5
x=-1
d) 2/3x- 4 2/3 = 2(x-3)
2\3x-42\3=2x-6
2\3x-2x=42\3-6
-1 1\3x=-2 2\3
x=7\4

a b) mi nie wychodzi
2009-12-28T16:29:40+01:00
A)
3x-3(2x-2)=3(x-2)
3x-6x+6=3x-6
-6x=-12
x=2

b)
2x-(8-x)=-2(x-5)
2x-8+x=-2x+10
2x+x+2x=10+8
5x=18
x=3 i3/5

c)
-5x+2(1-x)=-x-2(x+1)
-5x+2-2x=-x-2x-2
-5x-2x+3x=-2-2
-4x=-4
x=1

d)
2/3x-4 2/3=2(x-3)
2/3x-4 2/3=2x-6
2/3x-2x=-6+4 2/3
-1 1/3x=-1 1/3
x=1